Late Europeans and Melancholy Fiction at the Turn of the Millennium - Ellison, Ian. author. aut Link
XVII, 274 p.
Keywords: “In an account informed by Benjamin and Nietzsche, Ian Ellison explores the melancholy of late modernist fictions by Patrick Modiano, W. G. Sebald and Antonio Muñoz Molina. These epigonal fictions cross the threshold between fiction and history and are gathered here as works of detection which emphasize the pathos of their own epistemological failure. Although Ellison acknowledges that these novels communicate the exhaustion of European culture and the irreconcilable violence of its past, notably against its Jews, he proposes that a rejuvenation of the future is still possible. This book is a fresh and adeptly theorised work by an emerging scholar in comparative literary studies.” --Richard Robinson, Associate Professor of English, Swansea University, UK This book is the first comparative study of novels by Patrick Modiano, W. G. Sebald, and Antonio Muñoz Molina. Drawing on many literary figures, movements, and traditions, from the Spanish Golden Age, to German Romanticism, to French philosophy, via Jewish modernist literature, Ian Ellison offers a fresh perspective on European fiction published around the turn of the millennium. Reflecting on what makes European fiction European, this book examines how certain novels understand themselves to be culturally and historically late, expressing a melancholy awareness of how the past and present are irreconcilable. Within this framework, however, it considers how backwards-facing, tradition-oriented self-consciousness, burdened by a sense of exhaustion in European culture and the violence of its past, may yet suggest the potential for re-enchantment in the face of obsolescence. Ian Ellison divides his time as a DAAD PRIME postdoctoral research fellow between the University of Kent in Canterbury, UK, their Paris School of Arts & Culture, France, and the Goethe-Universität in Frankfurt am Main, Germany. This is his first book.